The effectiveness of marketing communications tools used by MPSJ in order to attract the residents to join the JKP / Zalifah Zulkifly - Zulkifly, Zalifah (Faculty of Business and Management, 2004)
Among the objective of the residents' committee or better known as Jawatankuasa Penduduk (JKP) is to coordinate the residents' committee activities and programmes, to implement and coordinate MPSJ Local Agenda 21, to manage the disbursement of funding to the residents' committee and to coordinate the "Mesra Rakyat" programmes. With such objectives, the residents will live in a comfortable manner. Therefore, the objective of this research is to study on the effectiveness of marketing communications tools used by MPSJ in order to attract the Residents to join the JKP. In order to complete this study, descriptive research is employed. Two approaches of collecting data are being used. The first approach is primary data such as questionnaires while the second approach is secondary data such as MPSJ Annual Reports, Bulletins, pamphlets, brochures and flyers (internal data), textbook, journals, published data sources, newspapers and Internet (external data). From the findings, the conclusion can be made is majority of the respondents chose advertising as the effectiveness of marketing communications tools as they are more exposed to the world of advertising. This is an important way to make the image of the JKP well established in the eyes of the residents. By doing an attractive and extensive promotion ofthe JKP, the residents will start to know what the JKP is all about.